SURAH AL-KAHFI AYAT 65: Ilmu Laduni Perspektif Ulama Muslim - Miftachurrozaq, Tahmid; Waharjani , Waharjani; Perawironegoro, Djamaluddin; Noto Sudarmo, Sarwono (Faculty of Ushuluddin and Religious Studies UIN Sulthan Thaha Saifuddin Jambi, 2023)
This study is a study of laduni science seen from various perspectives of Muslim scholars, with the background that not all stories in the Qur'an are arranged hierarchically as a giver of advice to mankind.. This study aims to provide an overview of the concept of laduni science from the perspective of Muslim scholars. This study uses a qualitative research design based on historical research and literature. Various reading materials, periodicals, and other references are used as data sources. The results of the study state that laduni knowledge is knowledge that is obtained without an intermediary between the soul and God. Nothing but the light that comes from a magic lamp that hits a clean, empty, and gentle heart A person who understands his own essence also understands his God. Laduni knowledge is not the result of magic that suddenly appears in someone's self; one must go through a process that is not easy to get this knowledge. Laduni knowledge is knowledge that comes directly from God without intermediaries, only from himself and God. Kajian ini merupakan telaah ilmu laduni dilihat dari berbagai sudut pandang para cendekiawan muslim, dengan dilatarbelakangi tidak semua kisah dalam Al-Qur’an tersusun secara hirarkis sebagai pemberi nasehat kepada umat manusia. Kajian ini bertujuan untuk memberikan gambaran tentang konsep ilmu laduni dari perspektif cendekiawan muslim. Penelitian ini menggunakan desain penelitian kualitatif berdasarkan penelitian sejarah dan literatur. Berbagai bahan bacaan, majalah, dan referensi lain digunakan sebagai sumber data. Hasil kajian menyatakan bahwa ilmu laduni adalah ilmu yang diperoleh tanpa perantara antara jiwa dengan Tuhan. Tak lain adalah cahaya yang berasal dari lampu ajaib yang menerpa hati yang bersih, kosong, dan lembut. Seseorang yang memahami hakikatnya sendiri juga memahami Tuhannya. Ilmu Laduni bukanlah hasil kesaktian yang tiba-tiba muncul dalam diri seseorang; seseorang harus melalui proses yang tidak mudah untuk mendapatkan ilmu ini. Ilmu Laduni adalah ilmu yang datang langsung dari Tuhan tanpa perantara, hanya dari dirinya sendiri dan Tuhan.